Efficient Lagrange multiplier selection algorithm for depth maps coding. Issue 20 (9th September 2016) - Huo, Junyan; Mo, Dongchun; Yang, Fuzheng; Lin, Weisi
Abstract : The rate–distortion optimisation criterion of depth maps coding is evaluated by virtual view distortion, which motivates research modelling the distortion and corresponding Lagrange multiplier for depth maps coding. Current studies follow the assumption that the virtual view distortion introduced by texture videos distortion and depth maps distortion can be explored separately. Then the texture‐videos‐distortion‐induced virtual view distortion is considered as a constant value during depth maps coding. A relationship between the optimal Lagrange multiplier of depth maps and texture videos distortion is investigated. Based on this relationship, an efficient Lagrange multiplier selection algorithm is proposed for depth maps coding based on quantisation parameters of texture videos and depth maps. With the proposed Lagrange multiplier, 1.36% bitrate saving with the same virtual view quality can be achieved compared with 3D high efficiency video coding reference software.